Pencatatan Laporan Keuangan Berbasis Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas (SAK ETAP) Pada Usaha Mikro Kecil Menengah (UMKM) di Bidang Jasa - Pristiana Widyastuti (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2017)
This study aimed to analyze the application of Financial Accounting Standards For Entities Without Public Accountability (SAK-ETAP) financial records on Micro, Small and Medium Enterprises (SMEs) in the field of services. SAK-ETAP is the financial standards that facilitate SMEs in preparing and presenting financial statements. Financial reports used by SMEs as information to investors and creditors to obtain business funding. The information can also be used as a reference for business tax reporting. This research is a descriptive study using a qualitative approach to SMEs in the field od services namely Bimbingan Belajar Disciple Course (Dis-Co). The study was conducted through qualitative data analysis developed by Milles and Huberman namely data reduction, data models and conclusions or verification. Data is collected by observation and in-depth interviews to stakeholders. The results showed that financial records are still done simply due to lack of knowledge of owner for the purpose, benefits and stage of preparation of financial statements based SAK-ETAP. Based on the research results, there should be counseling the application of financial report based on SAK-ETAP for SMEs. Keyword: Accountinng, SAK-ETAP, Financial Report, SMEs, Services